(untitled) (Research, Society and Development, 2023)
Objective: To analyze the landscape of scientific research between 2012 and 2022 on pharmaceutical care in childhood leukemia, aiming to understand trends, advancements, and gaps. Methods: An integrative literature review was conducted using specific descriptors in the following databases: Medical Literature and Retrieval System Online (MEDLINE/PubMed) via the National Library of Medicine; Latin American and Caribbean Literature in Health Sciences (LILACS) accessed through the Virtual Health Library (BVS); and the Scientific Electronic Library Online (SciELO) portal. Results: Eight articles related to the topic were selected, with 62.5% of the articles being literature reviews, 25% (2/8) data surveys, and 12.5% (1/8) clinical trials. Of these, only three literature reviews emphasized the importance of the pharmacist’s role in the treatment of childhood leukemia, while the other studies included the pharmacist in the multidisciplinary team without clearly highlighting their role. Conclusion: The pharmacist plays a crucial role in the care of children with ALL, participating in laboratory diagnostics, pharmacotherapeutic monitoring, early detection of complications, identification of toxicity, emotional support, and interprofessional interactions. However, there is a lack of recent studies on the subject, field research focusing on the pharmaceutical approach to the care of children with ALL, and works that integrate pharmacological therapy with complementary approaches and specialized nutrition. This identified gap suggests a promising area for future research.